The disrupted molecular circadian clock of monocytes and macrophages in allergic inflammation - Teppan, Julia; Schwanzer, Juliana; Rittchen, Sonja; Bärnthaler, Thomas; Lindemann, Jörg; Nayak, Barsha; Reiter, Bernhard; Luschnig, Petra; Farzi, Aitak; Heinemann, Akos; Sturm, Eva (Frontiers in Immunology, 2024)
Macrophage dysfunction is a common feature of inflammatory disorders such as asthma, which is characterized by a strong circadian rhythm. We monitored the protein expression pattern of the molecular circadian clock in human peripheral blood monocytes from healthy, allergic and asthmatic donors during a whole day. Monocytes cultured of these donors allowed us to examine circadian protein expression in human monocyte-derived macrophages, M1 and M2-polarized macrophages. In monocytes, particularly from allergic asthmatics, the oscillating expression of circadian proteins CLOCK, BMAL, REVERBs and RORs was significantly altered. Similar changes in BMAL1 were observed in polarized macrophages from allergic donors as well as in tissue resident macrophages from activated precision cut lung slices. We confirmed clock modulating, anti-inflammatory and lung protective properties of the inverse ROR agonist SR1001 by reduced secretion of macrophage inflammatory protein and increase of phagocytosis. Using a house dust mite model, we verified the therapeutic effect of SR1001 in vivo. Overall, our data suggest an interaction between the molecular circadian clock and monocytes/macrophages effector function in inflammatory lung diseases. The use of SR1001 leads to inflammatory resolution in vitro and in vivo and represents a promising clock-based therapeutic approach for chronic pulmonary diseases such as asthma.